Peran Hashtag #Indonesiabucketlist pada Konten Regram @Indtravel dalam Upaya Customer Engagement Marketing di Masa Pandemi Covid-19 - Hanggraito, Ahmadintya Anggit; Mahanani, Setya Mukti; Nulul, Noer Ayufika (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 02, Januari 2022DO - 10.24843/JUMPA.2022.v08.i02.p01, 2022)
Instagram becomes prominent social media that connect online communities to tourism destination although Covid-19 occurs. This study aims to explore the role of regram contents which are followed with #IndonesiaBucketList in Ministry of Tourism and Creative Economy of Indonesia Instagram official account, @indtravel. Data collected was the posts including photos, captions, comments, and likes, uploaded during the period of social restriction (PSBB) to emergency restriction (PPKM) for Java and Bali in third quarter of 2021. In particular, the present study examines customer engangement marketing model of @indtravel marketing practices in a time of crisis. Content analysis was employed in this qualitative descriptive study by identifying the regram contents posted with hashtag #IndonesiaBucketList. The results reveal that natural attraction category was the primary theme of the contents along with the most mentioned provinces, such as East Nusa Tenggara, Bali, Central Java, and East Java. It is also consistent that customer engagement cycle of @indtravel suggest customer engangement marketing practice is dealing with tourism crisis during Covid-19 pandemic. Keywords: Instagram, Social Media, Regram, Hashtag, Customer Engagement Marketing, Tourism Crisis.